Analysis of Compliance with Repairs of Hypertension Reviewed from Health Care Function and Implementation of Family Health Information Package - Ahmad Zainal Abidin (Journal for Quality in Public Health, 2019)
Treatment compliance with patients with hypertension is a very important concern to approach morbidity and mortality due to hypertension and to improve the quality of life of patients with hypertension. this condition is inseparable from the existence of families who provide support in the form of their functions and the role of health workers in providing adequate services. The purpose of this study was to analyze treatment adherence to hypertension recipients in terms of health care function and the implementation of family health information package in Bulu village, Balen Bojonegoro district. The design of this study is a quantitative cross sectional approach with a simple random sampling technique as many as 109 respondents with hypertension who received a guided program and data analysis techniques using ordinal regression statistical tests. The results of this study indicate that there are effects of health care function and implementation of family health information package on treatment compliance of hypertensive patients with p value of ordinal regression test of 0,000 which is less than α = 0.05, meaning that H0 is rejected and H1 is accepted. Health care function has an effect of 41.2% and the implementation of family health information package has an effect of 48.7%, and is influenced by other factors by 28.4%. The influence of the family in the form of health care functions and health workers in the form of implementing family health information package proves the value of good treatment compliance in patients with hypertension, because patients feel more attention from various parties both internal and external.